A Review Study on the Effect of Needle Punching Machine Parameters on the Filtration Efficiency of Non-woven Fabric used for Development of Face Mask - Tay, Poh Jing; Nasir, Siti Hana (Progress in Engineering Application and Technology, 2021)
The purpose of this research is to identify the most suitable set of non-woven fabric as mask material would be suggested at the end of this review study. This review study was conducted by searching based on data from others research and compiling the data through a series of papers. The literature search used 4 databases (Google scholar, SAGE, ScienceDirect, Elsevier) and 30 articles were identified. The data from the previous researcher were compared and analysis were made based on these studies. High needle penetration, high needling density and hollow cross-sectional shape of fibre were suggested for parameters for non-woven fabrics used for face masks production because it provided higher fabrics density, smaller pore size, lower porosity, higher air permeability and excellent water resistance. High air permeability provide greater breathability for face masks and excellent water resistance provide a barrier to avoid droplets passing through the face mask fabrics. However, the filtration efficiency of non-woven fabrics will drop slightly when fabric thickness decreased.